2008
DOI: 10.1056/nejmoa0802437
|View full text |Cite|
|
Sign up to set email alerts
|

Toll-like Receptor 3 and Geographic Atrophy in Age-Related Macular Degeneration

Abstract: BACKGROUND Age-related macular degeneration (AMD) is the most common cause of irreversible visual impairment in the developed world. Advanced AMD is comprised of geographic atrophy (GA) and choroidal neovascularization (CNV). Specific genetic variants that predispose for GA are largely unknown. METHODS We tested (i) for association between the functional toll-like receptor-3 (TLR3) variant rs3775291 (L412F) and AMD in European Americans and (ii) the effect of TLR3 L and F variants on the viability of human r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
148
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(156 citation statements)
references
References 35 publications
6
148
1
1
Order By: Relevance
“…Furthermore, TLR3 stimulation of RPE cells induced the secretion of various cytokines, chemokines, and adhesion molecules. Poly(I-C), a synthetic dsRNA, induced apoptosis via TLR3 in both human and mouse RPE cells (20,21). Thus, TLR3-mediated signaling triggered by dsRNA might play a role in retinal diseases.…”
Section: Abca4mentioning
confidence: 99%
“…Furthermore, TLR3 stimulation of RPE cells induced the secretion of various cytokines, chemokines, and adhesion molecules. Poly(I-C), a synthetic dsRNA, induced apoptosis via TLR3 in both human and mouse RPE cells (20,21). Thus, TLR3-mediated signaling triggered by dsRNA might play a role in retinal diseases.…”
Section: Abca4mentioning
confidence: 99%
“…Double-stranded RNA is a marker for viral infection that is recognized by TLR3 [2]. TLR3 triggers specific signaling pathways that culminate in the activation of NF-kB and IRF3 transcription factors, as well as apoptosis, enabling the host to mount an effective innate immune response through the induction of cytokines, chemokines, and other proinflammatory mediators [3,4]. The adjuvant role of poly I:C also requires TLR3 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas RIP1 acts as a multifunctional adaptor protein that regulates NF-kB-dependent inflammation, apoptosis and necrosis in TLR3 signaling, RIP3 has a more specific role, which induces necrosis through the formation of the pro-necrotic complex. 22,23 Although previous studies have shown that intraocular injection of polyinosinic-polycytidylic acid (poly(I : C)), a synthetic analog of dsRNA, induces TLR3-dependent retinal degeneration, 24,25 the downstream molecular and biological events were not elucidated. In this study, we examined the mechanism of cell death of RPE and photoreceptors in dsRNA-induced retinal degeneration and identified programmed necrosis to promote inflammation by regulating the release of intracellular DAMPs and to be crucial in dsRNA-induced retinal degeneration.…”
mentioning
confidence: 99%